The Influence of Beauty Influencers, Electronic Word of Mouth, Brand Image, and Price Perception on Wardah Skincare Purchasing Decisions among Gen Z in Purwokerto - Dinda Mely Isanti; Andhi Johan Suzana; Arinastuti Arinastuti (Sean Institute, 2026)
The purpose of this study was to analyze the influence of beauty influencers, electronic word of mouth, brand image, and price perception on Wardah skincare purchasing decisions among Gen Z in Purwokerto. The population in this study were all Gen Z who reside or are active in Purwokerto and have purchased and used Wardah skincare products. The sampling method used accidental sampling with a sample size of 110 respondents. Data analysis was carried out using multiple linear regression analysis. The coefficient of determination (R2) was 0.554, which means that the variables of beauty influencers, electronic word of mouth, brand image, and price perception were able to explain variations in purchasing decisions by 55.4%. The results of the F test showed that the model was suitable for use with an F count value (32.585) > F table (2.46) and a significance of 0.001 < 0.05. The T count values ​​of the variables were (5.215; 6.099; 4.955; 6.747). The implication of this research is the need for companies to initiate strategies that encourage active consumer engagement, such as user-generated content (UGC) campaigns to increase positive testimonials on social media. Companies also need to strengthen marketing messages that emphasize specific product benefits to sharpen the brand's image in consumers' minds.